Market-oriented smallholder agricultural development in Ethiopia - Hoekstra, Dirk (International Livestock Research Institute, 2011)
On 2 and 3 June 2011, the IPMS project organized a workshop: ‘Market-Oriented Smallholder Development: IPMS Experience-Sharing Workshop’. Here, project manager Dirk Hoekstra introduces the aims of the event that will focus on 'participatory market-oriented commodity development'.